Personality, dietary identity, mental and sleep health in vegans and vegetarians: A preliminary cross‐sectional study - Christle Coxon; Piril Hepsomali; Karen Brandt; David Vauzour; Adele Costabile (Health Science Reports, 2023)
Abstract Background and Aims Plant‐based diets have gained popularity over the past decade. However, research regarding mental and sleep health benefits of following plant‐based diets are conflicting. As there are associations between mental/sleep health and various personality traits, and personality may differ between individuals who follow different diets, in this preliminary study, we examined the associations between mental and sleep health and (i) personality and (ii) dietary identity in individuals who follow vegan and vegetarian diets. Methods Cross‐sectional data on sociodemographic, personality traits, dietarian identity, overall mental health, depression, anxiety, stress, and sleep quality were collected from 57 vegan/vegetarian participants between the ages of 18–40. Results After controlling for various sociodemographic and lifestyle factors, linear regression models revealed that (i) higher dietarian private regard was a significant predictor of better overall mental health, (ii) lower levels of extraversion and higher levels of empathy predicted depression, (iii) higher levels of neuroticism and empathy predicted anxiety, (iv) higher levels of neuroticism, dietarian centrality, and neuroticism × centrality predicted stress, (v) higher levels of conscientiousness, lower levels of dietarian centrality, but higher levels of personal motivation and dietary strictness, as well as conscientiousness × centrality, conscientiousness × personal motivation, and conscientiousness × strictness predicted better sleep quality. Conclusions These preliminary findings suggest that not only personality traits, but also dietary identity was indeed related to mental and sleep health in individuals who follow plant‐based diets.